O jogo de forças no futebol midiatizado: A nova relação entre clubes e repórteres setoristas - Silva, Leonardo Oliveira da (Universidade do Vale do Rio dos Sinos, 2017)
This research deals with the new relationship between football clubs and traditional media outlets, after the mainstream media processes have been a part of society. You start with the assumption that, favoured by the new communication devices and by knowing how to handle this new kind of media, football clubs have assembled their press offices and started, themselves, to produce new content. The clubs have stopped being only sources of information and became active members of the communicational world. That change made the whole relationship with mainstream media different, which created a dispute bewtween the media field and the sports field. By field, we use the concept formulated by Bordieu (2004), in which he claims they're autonomous spaces, with their own laws, both integrating a macrocosmos. We believe that this shift in football clubs and their relation to the media, from being a reactive to an active agent, provoked what Fausto Neto (2008) has defined as "zones of affectation" among sectors of a mediated society. We understand, as José Luiz Braga (2012) does, that the targets in which we must point our researches are in this new relations with society. To study this new relationship way involving football clubs, specialized reporters and the affectations that they cause in the journalistic process, we looked onto the cases of Sport Club Internacional and the newspaper Zero Hora, both from Porto Alegre, using content analysis as the main study methodology, along with exploratory research and interviews. From observing the material published at the club's official website and at ColoradoZH, we understand that the alterations in the relations between source and reporter are shifting the sports coverage at the traditional media outlets, and puting at the media scene a new member: the offical media of the football clubs.
Keywords: Jornalismo esportivo; Clubes de futebol; Repórteres setoristas; Disputa de campo; Midiatização; Sports journalism; Football clubs; Especialized reporter; Field dispute; Mediatization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação